MATHEMATICAL MODELING OF TUNED MASS DAMPER APPLICATION IN MITIGATING VIBRATIONS IN HIGHRISE BUILDINGS - Supriadi, Diki
The Tuned Mass Damper (TMD) is a crucial device for protecting tall buildings from damage caused by vibrations due to wind, earthquakes, and human activities. Given the potential for significant structural damage, this study aims to develop a mathematical model capable of determining the optimal parameters for the TMD, focusing on enhancing the building's resistance to various vibration frequencies. The initial model begins by representing the building's motion as a single-mass spring system, which is then expanded to include the TMD. Fourier Transform is used to analyze the system in the frequency domain, allowing for the identification of conditions where maximum displacement occurs, independent of time. After determining the TMD design parameters, numerical simulations were conducted against sinusoidal external forces and the El Centro earthquake to evaluate how these configurations affect the building's response. The simulation results demonstrate that the developed model effectively reduces vibrations, confirming that the chosen TMD configuration can successfully mitigate vibrations.